2007
DOI: 10.2174/092986607779117191
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the Effects of Glycation of Human Serum Albumin on L-Trp Binding

Abstract: Modification of proteins by nonenzymatic glycation is one of the underlying factors that contribute to the development of the complications of diabetes. Human serum albumin (HSA) is one of the major targets of interaction with glucose through the Maillard reaction. The effects of 1 and 5 mg/ml glucose concentrations, which are consistent with blood glucose levels found in diabetic patients, on human serum albumin were studied by circular dichroism and fluorescence spectroscopy in sodium phosphate buffer, pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…HSA glycation in patients affected by diabetes mellitus impairs both ligand binding and anti-oxidant properties (Bourdon et al, 1999;Sakata et al, 2002;Cohen, 2003;Van Campenhout et al, 2006;Barzegar et al, 2007;Faure et al, 2008a). Notably, the Cu(II) binding capacity of glycated HSA is lower than that of the non-glycated protein (Sakata et al, 2002).…”
Section: Human Serum Albumin Glycosylation and Glycationmentioning
confidence: 99%
See 2 more Smart Citations
“…HSA glycation in patients affected by diabetes mellitus impairs both ligand binding and anti-oxidant properties (Bourdon et al, 1999;Sakata et al, 2002;Cohen, 2003;Van Campenhout et al, 2006;Barzegar et al, 2007;Faure et al, 2008a). Notably, the Cu(II) binding capacity of glycated HSA is lower than that of the non-glycated protein (Sakata et al, 2002).…”
Section: Human Serum Albumin Glycosylation and Glycationmentioning
confidence: 99%
“…Moreover, the Fe(III)-binding anti-oxidant capacity of HSA is markedly reduced in diabetes mellitus patients (Van Campenhout et al, 2006). Lastly, binding and transport of Trp by glycated HSA is reduced (Barzegar et al, 2007).…”
Section: Human Serum Albumin Glycosylation and Glycationmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously studied the structural and thermodynamic properties of glycated HSA in the presence of glucose after 7 days of incubation [25,26] using fluorescence and circular dichroism techniques, in addition to measuring the tryptophanbinding of glycated HSA in the presence of glucose [27]. Although glucose is major metabolic sugar, in the glycation reaction pathway some AGEs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature reports focus on the application of fluorescence spectroscopy for characterization of glycated albumin [41] and for studying the effects of glycation on changes in binding and oxidation properties of albumin [42]. For example, fundamental studies measuring the fluorescence lifetimes of native and glycated albumin proteins (human serum albumin and bovine serum albumin) have revealed that the shorter lifetime (when the decay curve is fitted by double and triple exponential functions) is sensitive to the onset and the progression of glycation [43].…”
Section: Emergence Of Optical Sensing Approachesmentioning
confidence: 99%